2022
DOI: 10.1038/s41598-022-07602-9
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive assessment of harmful heavy metals in contaminated soil in order to score pollution level

Abstract: Soil-related problems have grown up to be a major threat to human society. Scientific evaluation is helpful to understand the status of soil pollution and provide reference to further work. In this situation, Liaoning Province, a typical industrial and agricultural province in Northeast China, was selected as a case study region. It reviewed 200 studies published between 2010 and 2020 and recorded related data of soil heavy metal. It used model method and index method to evaluate the agricultural region. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
35
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(37 citation statements)
references
References 34 publications
1
35
0
1
Order By: Relevance
“…Heavy metal pollution poses a serious threat to human health because of the high toxicity, environmental mobility, accumulation in the food chain, and lack of biodegradability of heavy metals (Fei et al, 2022; Szymańska‐Pulikowska et al, 2023; Wdowczyk & Szymańska‐Pulikowska, 2022). In addition, heavy metals persist long term in soil environment and can adversely affect soil fauna and flora through soil–microbial interactions and microbial processes (Kumar et al, 2019; Zhao et al, 2022). Heavy metals are a persistent stress that threatens the local ecosystem; studies have shown their impact on changes in microbial metabolic activity, population diversity, and soil microbiome abundance (Qian et al, 2023; Yang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Heavy metal pollution poses a serious threat to human health because of the high toxicity, environmental mobility, accumulation in the food chain, and lack of biodegradability of heavy metals (Fei et al, 2022; Szymańska‐Pulikowska et al, 2023; Wdowczyk & Szymańska‐Pulikowska, 2022). In addition, heavy metals persist long term in soil environment and can adversely affect soil fauna and flora through soil–microbial interactions and microbial processes (Kumar et al, 2019; Zhao et al, 2022). Heavy metals are a persistent stress that threatens the local ecosystem; studies have shown their impact on changes in microbial metabolic activity, population diversity, and soil microbiome abundance (Qian et al, 2023; Yang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Mining, textiles, paper, fertilizer, painting, and petroleum refining industries are considered the main drivers of industrial growth that contribute to the economy and enhance human well-being. Nonetheless, adverse industrial practices have heightened concerns related to water pollution since they are one of the primary contributors to heavy metal ion pollution in water bodies [1][2][3]. In order to avoid the contamination of public streams and water resources, heavy metals are only allowed to be disposed of in extremely low amounts in wastewater effluent.…”
Section: Introductionmentioning
confidence: 99%
“…Biotic and abiotic stresses are the major constraints in agriculture, and many metabolic and physiological changes occur in plant species under these conditions [1,2]. Heavy metals, such as chromium, cadmium, arsenic, lead, mercury, zinc, nickel and copper, are common pollutants in soils, are biologically toxic and could persist long-term in the soil environment [3][4][5]. The soil in various agricultural regions has been partially contaminated with heavy metals, resulting in the reduced availability of farmland [6][7][8].…”
Section: Introductionmentioning
confidence: 99%